Mapping China's Global Future Playing Ball or Rocking the Boat? - Axel Berkofsky (Pubblicazioni ISPI, 2020)
China's future role on the global stage hinges upon a mixture of strengths and weaknesses. Beijing's meteoric rise in economic terms has been coupled with increasing military expenditures and a more assertive foreign policy stance. But the country is also facing a potential backlash, exemplified by protests in Hong Kong. This Report sets out to explore some of the key aspects of China's regional and global foreign policy. It analyses the core tenets that motivate and shape China's preferences, ideals, and actions, and explores how they interact with its partners, allies, and rivals.